EFEKTIFITAS PELAYANAN AKADEMIK DARING TERHADAP KUALITAS PENYELESAIAN STUDI AKHIR MAHASISWA DI MASA PANDEMI COVID-19 (Studi Kasus Jurusan Teknik Perencanaan Wilayah dan Kota Fakultas Sains dan Teknologi UIN Alauddin Makassar Tahun 2021) - Mildawati, Titi (Jurnal Teknologi Pendidikan Madrasah, 2021)
Components in the completion of final student studies must work well together (students, lecturers and academic staff). Lecturers and academic service staff must provide effective services that can provide convenience for students in completing their study period even in the midst of the COVID-19 pandemic, for the purpose of achieving quality student success. However, the current pandemic condition requires that all series of academic activities be carried out online so that all parties involved must adjust and prepare both the facilities needed during online services and the strategies that will be taken in online services. Therefore, this article examines online academic services (administrative file management, final project guidance and final exams) on the quality of final student study completion during the COVID-19 pandemic (a case study of the Urban and Regional Planning Engineering Department of UIN Alauddin Makassar Year 2021). Then this article identifies academic services (administration, guidance and exams) online, then maps the obstacles and conveniences experienced during online academic activities, and looks at the quality of the results of online academic activities, and looks for the best solution in overcoming the obstacles experienced in order to give birth quality students. This type of research is descriptive qualitative using data collection methods with interviews and surveys, collecting data using interview guide research instruments and questionnaires made in the form of Google Form, then analyzing data using Miles and Huberman theory. Based on the results of the study, it was found that academic services (administrative file management) were effective, proposal and thesis guidance activities were not optimal because the guidance process was short so that messages were not conveyed properly and student absorption did not understand the intent of the supervisor's input, the difficulty experienced was the network. for students who are in areas far from the reach of the internet, and slow response. The convenience of online academic activities is cost, time and energy saving. All processes of online academic activities have positive and negative values, but the output of the process is expected to maintain the quality of student completion.